Customer Service in Influencing Perceptions of New Students and Services of Upt PMB University of Muhammadiyah Sidoarjo - Ainur Rochmaniah; Elnika Fajarini (Universitas Muhammadiyah Sidoarjo, 2020)
As an educational institution, the thing that must be considered is the quality of service. If educational institutions always pay attention to the quality of their services to prospective new students, it will have an impact on the image of the campus which can lead to an increase in the interest of prospective new students who will register at UMSIDA. This study aims to determine the effect of Customer Service on the perceptions of new students and services at UPT New Student Reception at Muhammadiyah University, Sidoarjo. This type of research is quantitative descriptive, the location in this study was at the University of Muhammadiyah Sidoarjo with a sample of 96 respondents taken using the Slovin formula. While the sampling technique is proportional random sampling. Data collection is done by distributing questionnaires and documentation. Data were analyzed by simple linear regression with the help of SPSS 16.0. The results of this study stated that there was a good influence Customer Service (X) on the perception (Y1) of new students by 82.4% and a good effect of Custumer Service on service (Y2) of new students by 81.2% at the UPT of New University Student Admissions Muhammadiyah Sidoarjo.